Bridging Urban and Rural Contexts: A Comparative Case Study of English Teachers’ Implementation of the Merdeka Curriculum - Rosyana Marlianti; Susi Astiantih; Syarif Hidayat Nasir; Zakaria Zakaria (Universitas Pendidikan Mandalika, 2026)
This study aims to explore and compare the implementation of the Merdeka Curriculum by English teachers in urban and rural junior high schools in Kolaka Regency, Southeast Sulawesi. A qualitative comparative case study method was employed, involving four English teachers from two schools—one urban and one rural. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using an interactive qualitative analysis framework that included data reduction, data display, within-case analysis, cross-case analysis, and conclusion drawing. The findings reveal notable differences in curriculum implementation practices and challenges across the two contexts. Urban teachers demonstrated pragmatic adaptation strategies, primarily focusing on material modification and internal collaboration within schools. In contrast, rural teachers exhibited high levels of pedagogical creativity and relied heavily on external collaborative networks, such as Musyawarah Guru Mata Pelajaran (MGMP). While both contexts faced pedagogical challenges, including low student motivation and limited vocabulary mastery, rural schools additionally encountered significant barriers related to inadequate digital infrastructure. This study underscores the importance of context-sensitive educational policies and targeted professional development programs to support equitable and effective implementation of the Merdeka Curriculum across diverse school settings.